PO 73 - The role of continuous spinal anesthesia on COVID-19 pandemic - Case Report - Marques, Ana; Barata, Melanie; Dias, Marta; Tiago, Catarina; Costa, Vânia (Journal of the Portuguese Society of Anesthesiology, 2023)
x